2014
DOI: 10.1186/1471-227x-14-21
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective descriptive study of the characteristics of deliberate self-poisoning patients with single or repeat presentations to an Australian emergency medicine network in a one year period

Abstract: BackgroundA proportion of deliberate self-poisoning (DSP) patients present repeatedly to the emergency department (ED). Understanding the characteristics of frequent DSP patients and their presentation is a first step to implementing interventions that are designed to prevent repeated self-poisoning.MethodsAll DSP presentations to three networked Australian ED’s were retrospectively identified from the ED electronic medical record and hospital scanned medical records for 2011. Demographics, types of drugs inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…In a larger cohort of adult overdose patients taking a wide range of medications, women represented 65% of patients presenting with DSP to our hospital network. 2,5 With paracetamol, this percentage was considerably higher in both adults and adolescents in the current study.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In a larger cohort of adult overdose patients taking a wide range of medications, women represented 65% of patients presenting with DSP to our hospital network. 2,5 With paracetamol, this percentage was considerably higher in both adults and adolescents in the current study.…”
Section: Discussioncontrasting
confidence: 44%
“…Although DSP is generally weighted towards the female sex as a form of intentional self‐harm, we found that adolescents ingesting paracetamol were even more likely to be women. In a larger cohort of adult overdose patients taking a wide range of medications, women represented 65% of patients presenting with DSP to our hospital network . With paracetamol, this percentage was considerably higher in both adults and adolescents in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In a Canadian study of hospitalised patients using illicit drugs, unstable employment, incarceration, daily heroin injection and younger age were associated with leaving against medical advice [27]. An Australian study of patients with deliberate self-poisoning found absconding patients more likely to have a mental illness and to be unemployed [28]. Among trauma patients in California, readmissions were more likely to be for psychiatric reasons following discharge against medical advice compared to regular discharge [3].…”
Section: Discussionmentioning
confidence: 99%
“…The association between mental illness and suicide, as well as repeat attempts, 28,29,30,31,32,33 has led to concern that recipients with self-inflicted injuries may have difficulty withstanding the rigors of the FT procedure and subsequent long-term treatment, particularly with regard to adherence. Inability to adhere to the post-transplant regimen can lead to adverse outcomes, including rejection and graft failure.…”
Section: Suicide and Risk Of Reinjurymentioning
confidence: 99%